2019
DOI: 10.1007/s40299-019-00494-w
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking Education in the Asian Pacific Region

Abstract: The importance of computational thinking (CT) education in the twenty-first century cannot be understated, as digital computing technologies have become an essential component of practically all human activities. Due to their strength in the ICT industry, countries such as Korea, Taiwan, Hong Kong, and China have launched national curricular reforms to address the current movement of CT education in K-12 education. This special issue, therefore, intends to provide insights into the current curricular reform mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 27 publications
1
33
0
5
Order By: Relevance
“…Berpikir komputasi akan membantu individu untuk memecahkan permasalahan umum yang kompleks melalui tahapan-tahapan decomposition, pattern recognition, abstraction, serta algorithm design (Hunsaker, 2020). Bahkan Wing (2006) menyebutkan bahwa berpikir komputasi menjadi kemampuan penting yang perlu dimiliki selain kemampuan membaca, menulis, dan aritmatika (So, Jong & Liu, 2020;Wing, 2006). Hal tersebut menunjukkan bahwa berpikir komputasi merupakan kemampuan yang bersifat fundamental yang perlu dipelajari dan digunakan oleh setiap orang.…”
Section: Pendahuluanunclassified
“…Berpikir komputasi akan membantu individu untuk memecahkan permasalahan umum yang kompleks melalui tahapan-tahapan decomposition, pattern recognition, abstraction, serta algorithm design (Hunsaker, 2020). Bahkan Wing (2006) menyebutkan bahwa berpikir komputasi menjadi kemampuan penting yang perlu dimiliki selain kemampuan membaca, menulis, dan aritmatika (So, Jong & Liu, 2020;Wing, 2006). Hal tersebut menunjukkan bahwa berpikir komputasi merupakan kemampuan yang bersifat fundamental yang perlu dipelajari dan digunakan oleh setiap orang.…”
Section: Pendahuluanunclassified
“…Heintz et al (2016) reviewed the introduction model of K-12 computer science education in 10 countries by analyzing the relevant documents for each country and found that the common model is to make computer science education compulsory in primary school and elective in secondary school. So et al (2020) introduced computational thinking education (computer science education) status in the Asian Pacific Region by reviewing five empirical studies and one literature review study and showed the current research trends in the field of computer science education and teachers' perception in the region. The second approach presents computer science education trends in worldwide or regions; however, little research has been conducted in terms of curriculum trend.…”
Section: Comparative Education Research On K-12 Computer Science Educationmentioning
confidence: 99%
“…The learning method is one of the most crucial factors in students' learning intention and learning style. During higher education teaching, it is critical to cultivate students' ability to analyze and solve problems [51,52]. Higher education represents the highest level of education; consequently, its content should cover not only specialized knowledge that reflects the latest developments in science and technology but also innovation in science and technology to promote the sustainable development of the social economy and culture [53,54].…”
Section: Test Of the Homogeneity Of Regression Coefficients Within Groupsmentioning
confidence: 99%